Situation Report: Czechoslovakia, 2 November 1981 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Prague Television Programs Discuss Polish Situation Five-Year Plan Delayed Romania Fails to Deliver Electricity Standard of Living to Suffer Personnel Changes with a Meaning? Change of Regional Party Secretary